Tibial segmental bone defect treated with bone plate and cage filled with either xenogeneic composite or autologous cortical bone graft - Teixeira, C. R.; Rahal, S. C.; Volpi, R. S.; Taga, R.; Cestari, T. M.; Granjeiro, J. M.; Vulcano, L. C.; Correa, M. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Tibia segmental defect healing in sheep were clinically, radiographically and histologically evaluated. Twelve young sheep aged four to five months were divided into two groups, G1 and G2. A 3.5 cm long segmental defect was created in the right tibial diaphysis with maintenance of the periosteum. The bone defects in both groups were stabilized with a bone plate combined with a titanium cage. In G1 the cage was filled with pieces of autologous cortical bone graft. In G2 it was filled with a composite biomaterial which consisted of inorganic bovine bone, demineralized bovine bone, a pool of bovine bone morphogenetic proteins bound to absorbable ultra-thin powdered hydroxyapatiteand bonederived denaturized collagen. Except for one G1 animal, all of them showed normal limb function 60 days after surgery. Radiographic examination showed initial formation of periosteal callus in both groups at osteotomy sites, over the plate or cage 15 days postoperatively. At 60 and 90 days callus remodeling occurred. Histological and morphometric analysis at 90 days after surgery showed that the quantity of implanted materials in G1 and G2 were similar, and the quantity of new bone formation was less (p=0.0048) and more immature in G1 than G2, occupying 51 ± 3.46% and 62 ± 6.26% of the cage space, respectively. These results suggest that the composite biomaterial tested was a good alternative to autologous cortical bone graft in this experimental ovine tibial defect. However, additional evaluation is warranted prior to its clinical usage.
Keywords: Bone defect; treatment; biomaterials; bone graft; sheep